2023
DOI: 10.1111/1541-4337.13242
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the intestinal toxicity of foodborne mycotoxins through gut microbiota: A comprehensive review

Haonan Ruan,
Ying Huang,
Binyang Yue
et al.

Abstract: Mycotoxins, which are fungal metabolites, pose a significant global food safety concern by extensively contaminating food and feed, thereby seriously threatening public health and economic development. Many foodborne mycotoxins exhibit potent intestinal toxicity. However, the mechanisms underlying mycotoxin‐induced intestinal toxicity are diverse and complex, and effective prevention or treatment methods for this condition have not yet been established in clinical and animal husbandry practices. In recent year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 268 publications
0
1
0
Order By: Relevance
“…These observations suggest that prolonged exposure to ZEN (which is also referred to as a mycoestrogen, a xenoestrogen, or an undesirable substance) is associated with tumors not only in the reproductive system [ 3 ] but also in the gastrointestinal tract [ 6 , 12 , 30 ]. According to Cieplińska et al [ 13 ] and Ruan et al [ 31 ], the processes observed in the gastrointestinal tract result from new mechanisms underlying mycotoxin-induced toxicity, which determine the quantitative and qualitative composition of key gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that prolonged exposure to ZEN (which is also referred to as a mycoestrogen, a xenoestrogen, or an undesirable substance) is associated with tumors not only in the reproductive system [ 3 ] but also in the gastrointestinal tract [ 6 , 12 , 30 ]. According to Cieplińska et al [ 13 ] and Ruan et al [ 31 ], the processes observed in the gastrointestinal tract result from new mechanisms underlying mycotoxin-induced toxicity, which determine the quantitative and qualitative composition of key gut microbiota.…”
Section: Discussionmentioning
confidence: 99%